Betaine for the prevention and treatment of insulin resistance and fatty liver in a high-fat dietary model of insulin resistance in C57BL mice - Kathirvel, Elango; Morgan, Kengathevy; Malysheva, Olga V.; Caudill, Marie A.; Morgan, Timothy R. (Frontiers in Nutrition, 2024)
The aim was to investigate mechanisms by which betaine improves hepatic insulin signaling in a dietary mouse model of insulin resistance and fatty liver.Methods: C57BL 6J mice were fed a standard diet (SF), a standard diet with betaine (SFB), a nutritionally complete high fat (HF) diet, or a high fat diet with betaine (HFB) for 14 weeks. In a separate experiment, mice were fed high fat diet for 18 weeks, half of whom received betaine for the final 4 weeks. Activation of insulin signaling in the liver was assessed by western blot.Insulin signaling was also assessed in insulin resistant primary human hepatocytes treated with betaine.Results: As compared with SF, mice receiving HF diet were heavier, had more hepatic steatosis, and abnormal glucose tolerance test (GTT). Betaine content in liver and serum was 50% lower in HF than in SF; betaine supplementation restored serum and liver betaine content.Betaine treatment of HF reduced whole body insulin resistance as measured by GTT. Betaine treatment of HF increased tyrosine phosphorylation of insulin receptor substrate-1 and phosphorylation (activation) of Akt, and increased hepatic glycogen content. In vitro, betaine reversed insulin resistance in primary human hepatocytes by increasing insulin-stimulated tyrosine phosphorylation of IRS1 and of Akt.Conclusions: Betaine supplementation reduced whole body insulin resistance and increased activation of insulin signaling pathways in the liver in a mouse model of insulin resistance and fatty liver created by feeding a nutritionally complete high fat diet for 14 weeks. Betaine also reduced liver injury as assessed by ALT and by liver histology. In vitro, betaine reversed insulin resistance by increasing insulin-stimulated tyrosine phosphorylation of IRS1 and activation of downstream proteins in the insulin signaling cascade in insulin resistant primary human hepatocytes.